Pengaruh Model Pembelajaran Problem Based Learning dan Minat Belajar terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik Kelas XI SMA - Mirna; Kaharuddin Arafah; Pariabti Palloan (Postgraduate, University of Mataram, 2025)
This study is a true experimental design study using a 2x2 factorial design. The purpose of the study is to: find out whether or not the application of the Problem Based Learning model and learning interest has an effect on the results of physics problem solving abilities of class XI MIPA, and to diagram the interaction of the learning model and learning interest on the results of physics problem solving abilities. The research data were obtained by providing a learning interest questionnaire sheet to students before being taught using the learning model in the study, and for the Problem Solving ability test results were carried out after students were taught using the learning model in the study. The data analysis technique used was analysis of variance (ANOVA). Based on the results of the inferential analysis obtained: F count (26.57) > F table 4, it can be concluded that there is a significant difference between students who are taught using the Problem based learning model and students who are taught using the discovery learning model; F count (0.53) < F table 4, it can be concluded that there is no interaction between the learning model and learning interest on the results of students' Problem Solving abilities.